27.5k views
5 votes
-w + 4(w+3) = -12

Please help

User Vojtech B
by
6.7k points

2 Answers

3 votes
I assume you want to solve for w. So, we will need to put w on one side and everything else another side.

-w + 4(w + 3) = -12 ; Our equation
-w + 4w + 12 = -12 ; Distribute the 4 across w and 3
3w + 12 = -12 ; Combine like terms, -w and 4w
3w = -24 ; Subtract 12 from each side of the equation
w = -8 ; Divide both sides by 3.

User Exilit
by
5.5k points
1 vote
Let's solve your equation step-by-step.−w+4(w+3)=−12Step 1: Simplify both sides of the equation.−w+4(w+3)=−12Simplify: (Show steps)3w+12=−12Step 2: Subtract 12 from both sides.3w+12−12=−12−123w=−24Step 3: Divide both sides by 3.3w3=−243w=−8Answer:w=8
User Pattu
by
6.0k points